Cover Image. Issue 7 (15th June 2018) - Angeli, T. R.; O'Grady, G.; Vather, R.; Bissett, I. P.; Cheng, L. K.
Abstract : The cover image, by T. R. Angeli et al., is based on the Original Article Intra‐operative high‐resolution mapping of slow wave propagation in the human jejunum: Feasibility and initial results, DOI:10.1111/nmo.13310 .